Factores que influyen en la utilización de los servicios de banca móvil en el Perú - Yamakawa, Peter (2013)
Mobile banking services are applications that can overcome the limitations of space and time of the banking activities. This study identifies the factors that influence consumer decisions of these services in Metropolitan Lima. To do this, we used an adaptation of the Technology Acceptance Model (TAM), which included external variables selected from previous studies. The results demonstrate that the compatibility with the lifestyle, the perceived usefulness, the perceived ease of use and the personal innovation in IT contribute to increase the intention to use these services.